Políticas de saúde no Brasil nos anos 2000: a agenda federal de prioridades Health policies in Brazil in the 2000s: the national priority agenda - Cristiani Vieira Machado; Tatiana Wargas de Faria Baptista; Carolina de Oliveira Nogueira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
O artigo analisa as prioridades da política nacional da saúde no período de 2003 a 2008, correspondente ao Governo Lula. A pesquisa envolveu revisão bibliográfica, análise documental, análise de dados e entrevistas com dirigentes federais. Foram identificadas quatro prioridades na agenda federal da saúde: a Estratégia Saúde da Família, o Brasil Sorridente, os Serviços de Atendimento Móvel de Urgência e o programa Farmácia Popular. A primeira configura uma política de alta densidade institucional, iniciada no governo anterior, constituindo um exemplo de "dependência da trajetória". As demais foram adotadas como marcos de governo e trouxeram inovações em áreas em que havia fragilidades da atuação federal. As quatro políticas prioritárias analisadas se voltam para problemas relevantes do sistema de saúde brasileiro, porém apresentam diferenças quanto à sua trajetória, base de apoio e implicações para os princípios do Sistema Único de Saúde. Apesar de mudanças incrementais, observou-se a predominância de elementos de continuidade na política nacional de saúde no período. This article analyzes Brazilian national health priorities from 2003 to 2008 under the Lula Administration. The study included a literature review, document analysis, and interviews with Federal health administrators. Four priorities were identified on the national health agenda: the Family Health Program, Smiling Brazil, Mobile Emergency Services, and the Popular Pharmacy Program. The first is a policy with high institutional density launched by the previous Administration, constituting an example of path dependence. The other three are innovations in areas where there had been weaknesses in Federal government action. The four policy priorities are strategies focused on solving key problems in the Brazilian health system. However, they display important differences in their historical development, political and institutional base, inclusion on the Federal agenda, and implications for the principles of the Unified National Health System. Although incremental changes have been introduced, national health policy has been characterized predominantly by continuity.